Pendidikan Karakter Anak di Jenjang SMP - Ika Ika; Fadilatul Jannah; Siti Subaekah; Ican Indrawan (Pusat Riset dan Inovasi Nasional, 2024)
Santri participated in building this nation as lost in the history of his people. Joko Widodo set National Day of Santri as a form of appreciation, considering the struggle of scholars and former santri contribute to the struggle for independence. 22 October was decided as National Day of Santri taken from the event of jihad resolution Hadratussyaikh Hasyim Asyari where defend his legal homeland fardlu ain. The purpose of this research is to know the implications of National Santri on the development of Islamic education in Indonesia. This research is done by qualitative approach using descriptive method. Data collection techniques include interviews, documentation, and literature studies. The result of the research shows that National Saving Day has not seen significant impact considering National Sdri Day has been running for two years, in the course of National Day of Santri is expected to restore the existence of santri and known to the wider community which in turn fosters the spirit of nationalism. The existence of National Saving Day is expected santri and Muslims in general have a high spirit in filling independence.